Improving civil aviation airports infrastructure taking into account the design process of aircraft maintenance organizations - Yu. I. Samulenkov; A. B. Babkov; Ya. A. Filatova (Научный вестник МГТУ ГА, 2022)
Air transport is of the essence in providing conditions for the effective performance of modern economic paradigm. Operating airlines, the subjects of the Russian Federation and the State as a whole, are equally interested in the development of air transportation system infrastructure. Civil aviation ensures the transport system integrated safety and stability, the relationship of regions and human settlements, especially Siberia, the North and the Far East regions. Over the post-Soviet period in the Russian Federation, the volume of passenger and cargo operations has decreased significantly, air transport linkages between regions have been lost. Such a passenger and cargo operations-related situation has occurred with heavy traffic congestion in the country’s hubs and does not allow the Russian Federation air transportation system to develop comprehensively and harmoniously. A detailed assessment of the country's civil aviation infrastructure will enable experts to put forward proposals for the air transport system modernization and development. Working space of aircraft maintenance organizations is an integral part among air transport infrastructure facilities. In order to conduct aeronautical equipment maintenance, it is necessary to have engineering and manufacturing objects, hangars and areas to accommodate and store maintenance facilities, equipment (general, individual, specialpurpose), consumables, premises for planning and dispatching departments, space to accommodate served aircraft, their components, etc. In addition, depending on the number of served aircraft types, the air transportation volume and regular pattern, the calculation of workforce and means of engineering and aviation support is essential. These issues require in-depth development on the basis of a scientific approach using the simulation modeling methods.